RECENT TECTONIC MOVEMENTS ON THE SUNDA FOREARC - C. Vita-Vinzi; B. Situmorang (Scientific Contributions Oil and Gas, 1990)
Geological fieldwork has been carried out by Lemigas – the University of London group in Nias and Simecular Islands in 1986 and 1987.